2021
DOI: 10.15376/biores.17.1.826-848
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the autoclave-assisted alkaline delignification of cocoa (Theobroma cacao) pod husks using KOH to maximize reducing sugars

Abstract: Cocoa pod husks are a type of biomass that is still poorly explored. This work was carried out as part of the optimization of the delignification process for this residue with potassium hydroxide, to maximize the reducing sugars content. Screening for potentially influencing factors showed that the biomass to solvent ratio and the temperature had the greatest effect on the delignification process. Optimization of these factors using a composite central plan revealed that the quadratic model was the most suitab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Prachayawarakorn Jutarat and Pattanasin Worawan, 2016 [ 50 ], identified the crystal structure of pectin from the β-helices located in the diffraction peaks at 18.6, 20.6, and 28.4°2ϴ. However, Adeleye et al, 2022 [ 51 ], and Ouattara et al, 2022 [ 58 ], mentioned that in the CPH flour, it is possible to superimpose the signal given by pectin at values between 20 and 23°2ϴ with the crystallinity peak of cellulose that can be located between 22.10 and 22.32°2ϴ. Continuing with the crystalline pattern of type I cellulose, Herrera-Barrios et al, 2022 [ 33 ], reported a cellulose content of 46.65% in the CPH flour, and the crystalline peaks were distributed between 15 and 17.7, 22, and 26.5, and between 34 and 35°2ϴ [ 36 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…Prachayawarakorn Jutarat and Pattanasin Worawan, 2016 [ 50 ], identified the crystal structure of pectin from the β-helices located in the diffraction peaks at 18.6, 20.6, and 28.4°2ϴ. However, Adeleye et al, 2022 [ 51 ], and Ouattara et al, 2022 [ 58 ], mentioned that in the CPH flour, it is possible to superimpose the signal given by pectin at values between 20 and 23°2ϴ with the crystallinity peak of cellulose that can be located between 22.10 and 22.32°2ϴ. Continuing with the crystalline pattern of type I cellulose, Herrera-Barrios et al, 2022 [ 33 ], reported a cellulose content of 46.65% in the CPH flour, and the crystalline peaks were distributed between 15 and 17.7, 22, and 26.5, and between 34 and 35°2ϴ [ 36 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…The processing of the results was done with the NEMROD version 2000 software. A factor is significance if its coefficient is greater than two times its standard deviation or two times the experimental error, according to equation ( 4) [4,5,[20][21][22][23].…”
Section: Ii3 Statistical Analysismentioning
confidence: 99%
“…After repetition of essay N°1, the respective experimental errors are 33.57 (iodine number) and 2.18 (methylene blue value). A coefficient is significant if in absolute value it is greater than twice the experimental error [4,5,[20][21][22][23]. By comparing the absolute value of the coefficients to their experimental error, we find that the factors carbonization temperature (U5) and the concentration of the activating agent (U6) influence the iodine number.…”
Section: Iii2 Estimates Of the Different Coefficientsmentioning
confidence: 99%
“…Similarly, an increase in the cellulosic fraction was observed at the expense of the hemicelluloses. This could be explained by the fact that in an alkaline environment, there is an increased dissolution of lignin, hemicelluloses, and extractives (Bensah et al 2019;Ouattara et al 2021;Bamba et al 2023).…”
Section: Characterisation Of the Raw And Delignified Substrate Extrac...mentioning
confidence: 99%
“…4 and 5. The texture of the raw CAB shows an irregular structure covered with wax, generally found on lignocellulosic materials (Daud et al 2013;Ouattara et al 2021). After processing, wax residues are also removed from the delignified structure.…”
Section: Scanning Electron Microscopy (Sem) Analysismentioning
confidence: 99%